Implementasi Prinsip Kehati-Hatian dalam Pengelolaan Lingkungan Permukiman Padat Penduduk: Studi Empiris di Rt 08 Rw 04 Malaka Jaya, Jakarta Timur - fitri indah nursanti (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Densely populated settlements are vulnerable to environmental degradation due to limited space, intensive domestic activities and pressure on environmental carrying capacity. This study aims to analyze the implementation of the precautionary principle in environmental management in densely populated settlements in RT 08 RW 04, Malaka Jaya, Duren Sawit District, East Jakarta. This research employs an empirical method with data collected through field observations and documentation. The results show that the precautionary principle has been implemented through water and waste management and community-based food security initiatives. However, its implementation has not yet been fully integrated into regional environmental management policies.